PERBEDAAN PROYEKSI PEMERIKSAAN RADIOGRAFI SINUS PARANASAL PADA KLINIS SINUSITIS DI RUMAH SAKIT MAYAPADA LEBAK BULUS. - Salsabila, Husniati; Hidayat, Wahyu; Nurbaiti, Nurbaiti; Sari, Gando (Universitas Tadulako, 2023)
Radiographic examination of the paranasal sinuses using an X-ray machine can be performed with various projections. Selection of the right projection will provide imaging results that support the diagnosis process. This study aims to analyze the management of the radiographic examination of the paranasal sinuses and to analyze the use of X-ray projections for the examination of the paranasal sinuses in patients with clinical sinusitis at Mayapada Hospital Lebak Bulus. This research method is descriptive qualitative with secondary data analysis approach in January 2022. The study sample consisted of six patients who underwent examination of the paranasal sinuses with clinical sinusitis. The research process includes literature study, observation and interviews. The instruments used are worksheets and documentation tools. Interviews were conducted with two radiographers and one radiology specialist. The result of this research is that the examination of the paranasal sinuses in clinical sinusitis can be performed using two or three projections. Examination of two projections, consisting of a parietoacanthial projection (water's method open mouth) and a lateral projection. Three-projection examination consists of lateral projection, parietoacanthial projection (water's method open mouth) and Posteroanterior or PA axial projection (caldwell method).